IMPLEMENTASI MODEL COURSE REVIEW HORAY DALAM PEMBELAJARAN TEMATIK INTEGRATIF PADA MOTIVASI BELAJAR SISWA KELAS V - Okta Prasetyani Susanti; Ika Septiani; Elis Dwi Purbiyanti (JS (JURNAL SEKOLAH), 2021)
Abstract : Implementation of the Course Review Horay Model in Integrative Thematic Learning on Learning Motivation of Class V Students. The purpose of the study was to determine the increase in learning motivation through the Course Review Horay (CRH) model in integrative thematic learning. The research subjects were fifth grade students of SDN 2 Menduran with a total of 26 students consisting of 17 girls and 9 boys. Data collection techniques were carried out using: questionnaires and post-test sheets which were processed using a simple quantitative analysis technique, namely the average score of the motivational questionnaire and classical learning completeness. The discussion in the study shows an increase in learning motivation as well as student learning outcomes to reach the minimum completeness criteria of 85% using the Course Review Horay (CRH) model. Students' learning motivation increases each cycle from cycle I to cycle III with learning outcomes, respectively, 53.85% (low), 69.23% (moderate) and 88.46% (high). While the increase in student motivation in each cycle was obtained 72.56%, 78.24%, and 85.10%.Keywords: Learning Motivation, Horay Course Review ModelAbstrak : Implementasi Model Course Review Horay Dalam Pembelajaran Tematik Integratif Pada Motivasi Belajar Siswa Kelas V. Tujuan penelitian adalah untuk mengetahuipeningkatan motivasi belajar melalui modelCourse Review Horay (CRH) dalam pembelajaran tematik integratif. Subjek penelitian adalah siswa kelas V SDN 2 Menduran dengan jumlah 26 siswa yang terdiri atas 17 perempuan dan 9 laki-laki. Teknik pengumpulan data dilakukan dengan menggunakan: angket dan lembar post tes yang diolah menggunakan teknik analisa kuantitatif sederhana yaitu nilai rata-rata skor angket motivasi dan ketuntasan belajar klasikal. Pembahasan dalam penelitian menunjukkan meningkatnya motivasi belajar sekaligus hasil belajar siswa hingga mencapai kriteria ketuntasan minimal sebesar ≥ 85% menggunakan model Course Review Horay (CRH). Motivasi belajar siswa meningkat setiap siklusnya dari siklus I sampai dengan siklus III dengan hasil belajar secara berturut-turut, 53,85% (rendah), 69,23% (sedang) dan 88,46% (tinggi). Sedangkan peningkatan motivasi siswa pada setiap siklus diperoleh 72,56%, 78,24%, dan 85,10%.Kata kunci : Motivasi Belajar, ModelCourse Review Horay